Sustainablity Analysis of Lombang Beach in Batang-Batang District, Sumenep City, Madura, East Java - Ivoni Firdausyah; Budi Setiawan; Agus Tjahjono (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Lombang beach is one of the best tourism places in Sumenep which has Spruce Shrimp trees (Casuarina equisetifolia) and extensive white refined sand as the icon. Lombang beach has potentials and benefits which can be developed, nonetheless, it couldn’t guarantee the sustainability of tourism, so that it needs to be studied for its sustainability extent. This research aimed to analyze the continuity of Lombang beach tourism based on four continuation dimensions such as ecology, economy, social, and infrastructure by using Multidimensional Scaling (MDS) which obtained through Rapid Appraisal for Lombang Beach Tourism (Rap-LBT) approach. The questionnaire was given to 54 tourists as respondents based on a nonprobability sampling (incidental sampling) approach. The sustainability analysis result presented that the sustainability of Lombang beach was quite sustainable. Ecological dimension has an index value of 57.93, economic dimension of 55.04, social dimension of 60.07 and infrastructure dimension of 50.68. The most sensitive attribute were regional arrangement, beach typical, tourism attraction, beach cleanliness, visit willingness, service quality, the cleanliness and quality of tourist facility, and public transportation for travel. Monte Carlo analysis result presented that the four dimensions were quite stable with the minor error extent for 95% of trusted standard.